The Effect of Internal Control and Auditor Competence on Fraud Prevention - Suyanto Suyanto; Benny Marcino; Sri Lestari Prasilowati; Indri Astuti; Maria Gayatri (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2022)
This study aims to determine the effect of internal control and auditor competence on fraud prevention on oil palm plantation. This research is an explanatory research with a quantitative approach. The method used in this study is a quantitative method using non-probability sampling with a purposive sampling technique through a rapid internet-based survey by distributing questionnaires (google form) through online media such as WhatsApp groups and social media (Instagram, Facebook, and twitter). The inferential statistics used are moderated regression analysis (MRA). This study uses internal control as an independent variable and auditor competence as a moderating variable. Internal control has an effect on fraud prevention. The implementation of internal control in the oil palm plantation industry is the key to fraud prevention which can serve as a guideline or Standard Operational Procedure (SOP) for stakeholders. Auditor competence is able to moderate the implementation of internal control towards fraud prevention. The auditor's understanding of the oil palm plantation business process as a whole can prevent fraud. The study focused on palm oil companies listed on the Indonesia Stock Exchange with auditor respondents having at least 5 years’ experience as an auditor for palm oil. This research contributes to providing information about fraud prevention in the oil palm plantation industry, so that it can be considered by management in developing a more effective fraud prevention detection model.